Taxonomy of Pimelodus brevis Marini, Nichols & La Monte, 1933 (Siluriformes: Pimelodidae), an uncertain species from the rio Paraná basin - Rocha,Marcelo Salles (2014)
Pimelodus brevisMarini, Nichols & La Monte, 1933 was described from the río de la Plata, Departamento San Fernando, Argentina, based only on the holotype, which is missing since 1960s. This species has been cited in the literature and is considered valid despite of no voucher specimen has been found in museum. A taxonomic analysis comprising material from the rio Paraná basin provided additional specimens that made it possible to demonstrate the identity of P. brevis. Based on the original description and illustration of the holotype, we performed an allometric analysis and then we were able to compare the data with the similar sympatric congeners. Those comparisons allowed us to conclude that P. brevisis a junior synonym of P. argenteusPerugia, 1891, described from the río Paraná, Colonia Resistencia, Argentina. Comments on the status of congeners and taxonomic recommendations are provided.